Association of AKR1C3 Polymorphisms with Bladder Cancer - Tiryakioglu, N. Ozan; Tunali, Nagehan Ersoy (Urology Journal, 2016)
Purpose: Polymorphisms in the genes coding for the carcinogen metabolizing enzymes may affect enzyme activities and alter the activation and detoxification rates of the carcinogens. AKR1C3 is one of the very polymorphic xenobiotic metabolizing enzymes involved in the bioactivation process. Here we aimed to investigate the association of two single nucleotide polymorphisms in AKR1C3, rs12529 (c.15C > G) and rs1937920 (12259 bp 3’ of STP A > G) with urinary bladder cancer (UBC). Materials and Methods: Two-hundred fifty UBC cases and 250 control subjects were genotyped using the Polymerase Chain Reaction and Restriction Fragment Length method. Associations of the genotypes with UBC risk and tumor characteristics were assessed using logistic regression and Fisher’s exact test. The results are corrected for multiple testing. Results: We identified strong associations between the studied AKR1C3 variants and UBC risk. The homozygous variant genotype of rs12529 was found to be inversely associated with UBC, and rs1937920 was shown to be associated with increased risk of UBC. None of the genotypes were found to be significantly associated with tumor characteristics. Conclusion: We provided evidence that rs12529 and rs1937920 are significant in the molecular pathogenesis of UBC. However, the results presented here should be regarded as preliminary and might represent a first step of future larger studies aiming to better elucidate the role of AKR1C3 polymorphisms in the susceptibility to bladder cancer.